IMPACT OF TASK PERFORMANCE ON JOB SATISFACTION OF IT EMPLOYEES - Veeraragavan, P.; Arulkumar, Dr. S. (The journal of contemporary issues in business and government, 2021)
By distributing a well-structured questionnaire to 200 employees chosen at random, this descriptive research assesses and understand the depth of task performance and job satisfaction that is predominant among employees in the Software Industry, as well as investigate the impact of task performance on job satisfaction. Numerous statistical techniques such as the Mean, Independent samples t-test, ANOVA, and Regression Analysis were utilised to examine the acquired data using inferential statistics. When IT personnel incorporate task performance in the course of their work, the study found that they are quite happy with their jobs. Employees with less education, lower income levels, and those in lower job cadres report lower levels of job satisfaction, whereas those with less work experience, age, education, income, job cadre, and male employees report lower levels of task performance. Task Performance has a substantial beneficial influence on job satisfaction, according to the findings of the study.